Effects of Different Dietary Protein Levels on the Growth Performance, Serum Biochemical Parameters, Fecal Nitrogen, and Carcass Traits of Huanjiang Mini-Pigs - Zhao, Xichen; Liu, Yating; Ding, Hao; Huang, Pan; Yin, Yulong; Deng, Jinping; Kong, Xiangfeng (Frontiers in Veterinary Science, 2021)
Huanjiang mini-pig is a Chinese local breed and the optimal dietary crude protein (CP) level for this breed is still unknown. Therefore, the present study was conducted to investigate their optimum dietary CP level upon the growth performance, serum biochemical parameters, fecal nitrogen content and carcass traits. Three trials independent with 360 pigs were included. A total of 220 pigs (5.32 ± 0.46 kg) were fed ad libitum either a 14%, 16%, 18%, 20%, or 22% CP diet from about 5 to 10 kg (trial 1), 84 pigs (11.27 ± 1.43 kg) were fed either a 12%, 14%, 16%, 18%, or 20% CP diet from about 10 to 20 kg (trial 2); and 56 pigs (18.80 ± 2.21 kg) were fed either a 10%, 12%, 14%, 16%, or 18% CP diet from about 20 to 30 kg (trial 3). In trial 1, as dietary CP levels increased, the feed to gain ratio (F/G) quadratically decreased and was minimal at 18.42% CP level. The average daily feed intake (ADFI) and final body weight (BW) were not affected by dietary CP levels while the fat percentage decreased. Besides, a linear decrease in slaughter rate and a linear increase in bone percentage, serum urea nitrogen (UN), and fecal nitrogen content of pigs were observed. In trial 2, as dietary CP levels increased, the average daily gain quadratically increased and was maximum at 16.70% CP level. The slaughter rate linearly decreased whereas the skin rate, serum UN, and NH3-N increased linearly, as well as fecal nitrogen content. In trial 3, as dietary CP levels increased, the F/G increased, while the ADFI and ADG quadratically decreased and was maximum at nearly 14.00% CP level. The bone percentage and serum UN increased linearly but the slaughter rate decreased linearly, and the fecal nitrogen content quadratically decreased whereas the albumin increased quadratically. Taken together, the optimal dietary CP levels for growth performance of Huanjiang mini-pigs from 5 to 10 kg, 10 to 20 kg, and 20 to 30 kg were 18.42%, 16.70%, and 14.00%, respectively.